2018
DOI: 10.1016/j.ebiom.2018.08.011
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism of SRRM4 in promoting neuroendocrine prostate cancer development via a pluripotency gene network

Abstract: Background Prostate adenocarcinoma (AdPC) cells can undergo lineage switching to neuroendocrine cells and develop into therapy-resistant neuroendocrine prostate cancer (NEPC). While genomic/epigenetic alterations are shown to induce neuroendocrine differentiation via an intermediate stem-like state, RNA splicing factor SRRM4 can transform AdPC cells into NEPC xenografts through a direct neuroendocrine transdifferentiation mechanism. Whether SRRM4 can also regulate a stem-cell gene network for NEPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
77
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(80 citation statements)
references
References 51 publications
(116 reference statements)
2
77
1
Order By: Relevance
“…Interestingly, this SRRM4‐directed RNA splicing profile shares a similar pattern to the diverse alternative splicing patterns seen in the neural system during development, where SRRM4‐spliced target genes have recognized functions that are crucial for neural programs early in development . Furthermore, our studies have reported that this reprogrammed RNA splicing signature is unique to NEPC patient tumors, PDX models, and cell models, indicating a clear variance in the phenotype of NEPC and AdPC tumors . The SRRM4‐driven t‐NEPC‐specific reprogramming of the transcriptome modifies anti‐apoptotic factors (eg, Bif‐1), epigenetic modifiers (eg, MEAF6‐1), and transcriptional regulators (eg, REST, FOXA1) that are important for regulating cell survival, proliferation and tumorigenesis, and neural differentiation, respectively .…”
Section: Introductionsupporting
confidence: 60%
See 4 more Smart Citations
“…Interestingly, this SRRM4‐directed RNA splicing profile shares a similar pattern to the diverse alternative splicing patterns seen in the neural system during development, where SRRM4‐spliced target genes have recognized functions that are crucial for neural programs early in development . Furthermore, our studies have reported that this reprogrammed RNA splicing signature is unique to NEPC patient tumors, PDX models, and cell models, indicating a clear variance in the phenotype of NEPC and AdPC tumors . The SRRM4‐driven t‐NEPC‐specific reprogramming of the transcriptome modifies anti‐apoptotic factors (eg, Bif‐1), epigenetic modifiers (eg, MEAF6‐1), and transcriptional regulators (eg, REST, FOXA1) that are important for regulating cell survival, proliferation and tumorigenesis, and neural differentiation, respectively .…”
Section: Introductionsupporting
confidence: 60%
“…The BPH‐1 cell line was provided by Dr Simon Hayward (Vanderbilt University, TN, USA). The LnNE and DuNE cell models, along with their control cells, were previously established by our group . All cell‐culturing conditions have been previously reported …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations